ALOKASI WAKTU JENDER DALAM RUMAH TANGGA NELAYAN BUDIDAYA RUMPUT LAUT DI KABUPATEN BUTON UTARA SULAWESI TENGGARA - Rosmawati .; La Rianda; St. Aida Adha Taridala (Program Studi Agrobisnis Perikanan, Fakultas Perikanan dan Ilmu Kelautan, UHO, 2016)
Time allocation of gender in the household of the seaweed farmers in Buton Utara Southeast Sulawesi.The present study is aimed time allocation of seaweed farmer households in their productive and social activities based on gender category. The population of the study was seaweed farmers amount 246 households, and 71 households were taken as samples. This study concerns with gender perspective as both husband and wife in cach household were interviewed thus, the sample became 142 respondents. The research was uji-t statistical analysis. The uji-t analysis showed that there was a significant different between husband and wife in productive, reproductive, and social activities. Meanwhile, both husband and wife contributed nearly the same amount of time in productive activities outside their main farming activities.Keywords: Time Allocation, Gender, Sea Weed